THE 1000 HARI PERTAMA KEHIDUPAN PROGRAM AS AN EFFORTS TO EMPOWER THE PERCENTAGE OF POOR NUTRITION IN BANGKALAN MADURA DISTRICT (the Aspects of Problem Characteristics, Policy Characteristics, and Policy Environment) - Eliviana Ary Risyananda; Ekky Fiorentina Asterix; Erna Setijaningrum (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
Bangkalan Regency was the region that contributed to the highest cases of malnutrition in East Java in 2018. The Bangkalan Regency Government has implemented the 1000 Hari Pertama Kehidupan program which is a mandate from the Peraturan Presiden Nomor 42 Tahun 2013 concerning the National Movement for the Acceleration of Nutrition Improvement. However, in its implementation, the 1000 Hari Pertama Kehidupan program still encounters many obstacles so that the implementation is not optimal. This study aims to examine the 1000 Hari Pertama Kehidupan program by reviewing the aspects of problem characteristics, policy characteristics, and policy environment using the implementation theory proposed by Daniel A. Mazmanian and Paul A. Sabatier. The method used is a descriptive qualitative approach using data collection techniques through five sources, including archival documents, in-depth interviews, participant observation, and other physical devices. The informant determination technique was carried out by purposive sampling and the number of informants was 10 people. The results showed that the implementation of the 1000 HPK program in tackling malnutrition in the Bangkalan Regency was not optimal. In terms of characteristics, the problem has a fairly high level of technical difficulty and the behavior of the target group is not right. In terms of policy characteristics, program objectives have not been optimally achieved, financial resources are limited, coordination between implementors is not optimal, and the Bangkalan Regency Government does not yet have binding decision rules between OPDs. Then in terms of the policy environment, social, economic, and technological conditions have not supported program implementation, and public support has not been optimal.